“Peace Lecture”: Curricular Proposal to Strengthen Coexistence - Betancourt Rodríguez, Milton Andrés; Triana Rivera, Reyes; Torres Quitora, Luis Fernando (Rastros Rostros, 2017)
Introduction: This article is a curricular proposal for a peace lecture to strengthen the healthy coexistence of students, based on Law 1732 of 2014, which systematizes and contextualizes the reality, objectives, principles and methodological and didactic foundations that must be adopted by each institution (P,1). Materials and methods: Qualitative research. The results are achieved through surveys and interviews of students and teachers, which demonstrate the importance of implementing the curricular proposal for a peace lecture that helps to reduce school conflicts and strengthen coexistence among classmates. Results: It was observed that the implementation of a peace lecture through the activities and workshops carried out, and the use of ict , reduced school conflicts among students. Conclusion: A peace lecture should focus on education as a primary factor for students through the proper management of the principles of peace, peace education and school conflicts, as well as the causes and consequences that have been identified in the research.